Dukungan Psikososial Keluarga bagi Ibu Hamil dan Menyusui di Wilayah Terdampak Erupsi Semeru melalui Program Mother Support Group - Hayati, Nurul; Candra Dewi, Novela Eka; Musviro, Musviro (Unity Academy, 2025)
Pregnant and breastfeeding mothers are vulnerable groups experiencing significant psychosocial stress in post-disaster situations. The Semeru eruption disrupted social, emotional, and health service access, affecting maternal and infant well-being. Objective: This community service aimed to improve psychosocial well-being of pregnant and breastfeeding mothers through strengthening family support using the Mother Support Group (MSG) approach. Methods: The program was conducted in Supiturang Village, Pronojiwo District, Lumajang Regency, involving six participants (pregnant mothers, breastfeeding mothers, and family members). Activities included sharing discussions, emotion card facilitation, family psychosocial education, and non-pharmacological relaxation techniques. Results: The MSG program enhanced emotional communication, reduced anxiety, and increased feelings of calmness and happiness among participants. Families demonstrated improved understanding and active involvement as key support systems. Conclusion: The Mother Support Group is an effective community-based intervention model to strengthen family psychosocial support for pregnant and breastfeeding mothers in disaster-affected areas.